2000
DOI: 10.1212/wnl.54.12.2316
|View full text |Cite
|
Sign up to set email alerts
|

Facial frequency manipulation normalizes face discrimination in AD

Abstract: People with AD have deficient contrast sensitivity and impaired face discrimination. The authors presented photographs of unfamiliar faces of three different sizes to enhance the low, middle, or high facial frequency information (cycles per face). Patients with AD demonstrated normal discrimination of small faces only, indicating that impaired contrast sensitivity at low facial frequencies contributes to their poor face discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…However, we excluded studies where prosopagnosia was a symptom of a more global deficit such as in cases of neurodegenerative disease (Cronin-Golomb et al, 2000; Turan et al, 2013) and autism spectrum disorder (Weigelt et al, 2012). …”
Section: Methods Of Search and Selection Criteriamentioning
confidence: 99%
“…However, we excluded studies where prosopagnosia was a symptom of a more global deficit such as in cases of neurodegenerative disease (Cronin-Golomb et al, 2000; Turan et al, 2013) and autism spectrum disorder (Weigelt et al, 2012). …”
Section: Methods Of Search and Selection Criteriamentioning
confidence: 99%
“…These visual capacities include color discrimination, especially on the blue-yellow axis, 17,[19][20][21] and contrast sensitivity. [17][18][19][22][23][24][25][26] Reductions in contrast sensitivity alone have been linked with numerous perceptual, cognitive, and behavioral abnormalities in AD. 18,[27][28][29] In normal observers, increased stimulus contrast is associated with decreases in search time, number of fixations per search, and fixation duration.…”
mentioning
confidence: 99%
“…For most people, contrast sensitivity is less acute at low and high relative to mid-range frequencies, producing the characteristic contrast sensitivity curve. Many investigators have reported contrast sensitivity deficits in AD patients [1][2][3][4][23][24][25][26][27][28], but the extent of impairment varies from study to study. In our recent investigation [7], we examined the two main potential explanations for such variability in the degree of impairment besides sample differences: acuity differences between AD and control groups, discussed above, and choice of assessment methods.…”
Section: Contrast Sensitivitymentioning
confidence: 99%
“…Deficits in spatial frequency contrast sensitivity result in increased difficulty in face discrimination in healthy elderly individuals [e.g., 29] and especially in patients with AD [24,28]. As described above, the spatial frequency of conventional grating stimuli is measured in cpd.…”
Section: Contrast Sensitivity Relation To Face Discriminationmentioning
confidence: 99%
See 1 more Smart Citation